The shape of night : [large type] a novel - Gerritsen, Tess (Center Point Large Print, 2020)
"A woman trying to outrun her past is drawn to a quiet coastal town in Maine--and to a string of unsolved murders--in this haunting tale of romantic suspense from New York Times bestselling author Tess Gerritsen"--Provided by publisher.